Multinationals from Emerging Countries: Internationalization of Brazilian Companies between 1970 and 2013 - Dalla Costa, Armando (2014)
In recent years, an increasing number of Brazilian companies have begun to operate abroad. Several factors contributed to this – most importantly, a new approach adopted by the Brazilian government that directly promotes international expansion through the National Bank for Economic and Social Development (BNDES). The purpose of this paper is to provide a long-term perspective on how these economic groups were created, as well as their activities from 1970 to 2013. In order to understand the internationalization of Brazilian companies and their operations during the early 21st century, this article seeks to answer questions such as: what advantages does Brazil have for the creation of multinational companies? What advantages were developed by the companies themselves that make them competitive on the international market? A preliminary conclusion derived from this analysis is that it was the combination of the advantages provided by Brazil and those developed by the companies themselves that led to these capacities and competitiveness on the international level.